Avaliação oromiofuncional e acompanhamento de lactentes com anquiloglossia - Portalupi, Diovana dos Santos (2022)
Objective: to evaluate and monitor the oromyofunctional development of infants with ankyloglossia before and after lingual frenotomy. Methods: infants with altered frenulum were reassessed using the protocol proposed by Martinelli et al (2013), and monitored for oromyofunctional development. Results: 82.4% of infants who arrived with dubious frenulum when applying the complete protocol, obtained frenulum interference scores on tongue mobility and were referred for frenotomy. Infants who underwent frenotomy had better responses regarding tongue anatomy, function and position after frenotomy. In the second evaluation after the frenotomy, the non-nutritive sucking went from 100.0% inadequate to 80.0% adequate, no more episodes of choking and tiredness were identified when breastfeeding, going from 60.0% to 100.0%, the shape of the tip of the tongue when raised during crying became rounded and the fixation of the frenulum on the sublingual surface of the tongue started to be located in the middle third. Conclusion: it was observed that infants with altered frenulum present changes in various aspects of the oromyofunctional system with consequences for breastfeeding, highlighting the importance of a specialized look at this population and a segment of these infants, in order to avoid early weaning. and thereby provide better development.